DAMPAK DARING DALAM MENGHAFAL QURAN PADA MASA PANDEMI COVID 19 DI SD PLUS JABAL RAHMAH MULIA KECAMATAN MEDAN SUNGGAL KOTA MEDAN - Datmi, Muhammad Akbar Rosyidi; Sumantri, Yogi; Kumala, Kirani; Muharaini, Desi (Al-I'jaz: Jurnal Kewahyuan Islam, 2021)
ABSTRACTThe Covid-19 virus pandemic that has shocked the world affects all aspects of life, whether political, economic, social and educational. During this pandemic, many schools were forced to close and were forced to go online. In the era of the New Normal life order, several schools and education-based foundations were opened and carried out offline and online learning. One of them is SD Plus Jabal Rahmah Mulia Medan. SD Plus Jabal Rahmah Mulia Medan is an educational foundation based on Tahfizhul Quran and Akhlakul Karimah. At the beginning of the pandemic, the foundation took a policy (holidaying students as an effort to prevent the spread of the virus and carry out online learning then the foundation issued a policy due to several considerations, namely by carrying out offline and online learning by observing health protocols. The purpose of this study was to find out how the impact of the pandemic for students in memorizing the quran to create a generation of people who are qurani and have good morals. The method used in this study is a qualitative method with interviews, observations and distributing questionnaires through the homeroom teacher to be sent to class VI students via online, namely class Abu Bakar, Umar bin Khattab, Uthman bin Affan and Ali bin Abi Talib. This report is descriptive in nature, namely explaining the problem of the questionnaire that has been distributed to students and interviews with several sources. The results of this study are to find problems from the impact of the limited pandemic What are the memorizers of the Quran at SD Plus Jabal Rahmah Mulia and the things that hinder students from memorizing the Koran.Keywords: Online and Offline, Tahfizhul Quran, Covid 19, Pandemic Impact